2018
DOI: 10.4103/ijem.ijem_575_17
|View full text |Cite
|
Sign up to set email alerts
|

Relation of bone mineral density with homocysteine and cathepsin K levels in postmenopausal women

Abstract: Background:Homocysteine (HCY) interferes with collagen cross-linking in bones and stimulates osteoclast activity. The activated osteoclasts secrete cathepsin K (CathK), a cysteine protease, in eminent quantity during bone resorption. Hyperhomocysteinemia may effect bone mineral density (BMD) through CathK. We, therefore, examined the relation between HCY and BMD along with CathK, 25-hydroxyvit-D (25[OH]D), intact parathyroid hormone (iPTH), and Vitamin B12.Materials and Methods:We recruited a total of 93 postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…While some studies show significant negative correlation of Hcy with BMD, some studies do not show such correlation. [10][11][12] Present study did not show any difference in calcium, phosphorous and alkaline phosphatase between different BMD groups which is in accordance with different studies by Massé. 13 Though there is a slight negative correlation of calcium with age it is not statistically significant, which is in concordance with the study by Onyeukwu et al 14 High serum homocysteine levels (Hyperhomocysteinemia HHcy) has been implicated as a risk factor for osteoporosis and osteoporotic fractures.…”
Section: Discussionsupporting
confidence: 90%
“…While some studies show significant negative correlation of Hcy with BMD, some studies do not show such correlation. [10][11][12] Present study did not show any difference in calcium, phosphorous and alkaline phosphatase between different BMD groups which is in accordance with different studies by Massé. 13 Though there is a slight negative correlation of calcium with age it is not statistically significant, which is in concordance with the study by Onyeukwu et al 14 High serum homocysteine levels (Hyperhomocysteinemia HHcy) has been implicated as a risk factor for osteoporosis and osteoporotic fractures.…”
Section: Discussionsupporting
confidence: 90%
“…found that homocysteine was not related to bone loss in postmenopausal women [34,35]. In this study, homocysteine levels in the low plasma folate and vitamin B 12 group were significantly higher than those in the high plasma folate and vitamin B 12 group; however, homocysteine levels were not related to bone loss.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, no correlation was observed between the serum homocysteine values and BMD, T-scores, or BMI. Two other studies reinforced this finding, thus demonstrating that serum homocysteine levels were not associated with BMD at either the femoral neck or the lumbar spine and that the associations between the homocysteine levels and fracture risk noted in previous studies were independent of BMD [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 69%